Navigating Change: An Analysis of Elementary School Teachers' Readiness and Implementation Challenges with the Merdeka Curriculum - Cucun Sutinah; Arie Rakhmat Riyadi; Agni Muftianti; Medita Ayu Wulandari; Siti Ruqoyyah (AL-ISHLAH: Jurnal Pendidikan, 2024)
Education is a central pillar in forming the foundation of society's future, and implementing a relevant curriculum is critical in ensuring the quality of learning. As a response to increasingly complex educational challenges, the Merdeka Curriculum focuses on developing competence and character with essential material. On the other hand, the Merdeka Curriculum also offers teachers flexibility in designing and implementing learning according to student needs and local context. This research aims to explore and analyze the implementation of the Merdeka Curriculum among elementary school teachers as a reflection to provide effective feedback. The survey method is used to collect data through questionnaires that have been developed and have undergone expert validation. Questionnaires were distributed to 160 state elementary school teachers in West Bandung Regency. The questionnaire includes 7 question items about teacher readiness, level of understanding of the Merdeka Curriculum, and identification of obstacles and strategies for overcoming them. The data collected was analyzed quantitatively using a descriptive statistical approach. The research results show that teachers are ready to implement the Independent Curriculum but their understanding is still limited which has an impact on the presence of challenges in its implementation. These findings have implications for the urgency of increasing teachers' understanding regarding the Independent Curriculum, skills in designing and implementing learning in accordance with the characteristics of the Independent Curriculum, including assessment. With better understanding and skills, the challenges faced will be overcome.